2014
DOI: 10.1167/iovs.14-14606
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Alters Cx43 Expression and Gap Junction Intercellular Communication in Retinal Müller Cells: Promotes Müller Cell and Pericyte Apoptosis

Abstract: Gap junction communication between Müller cells and pericytes is essential for their survival. Downregulation of Cx43 that is HG induced and impairment of GJIC activity in Müller cells contributes to loss of glial and vascular cells associated with the pathogenesis of diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 50 publications
(64 reference statements)
2
39
0
1
Order By: Relevance
“…100 glucoseeinduced changes in Cx43 expression in human DR, and the potential application of this knowledge in the treatment of DR, is only beginning to be understood. Our findings demonstrated that high glucoseeinduced Cx43 up-regulation may have protective effects on retinal Müller cells, 99 whereas a decreased level of Cx43 alone is sufficient to induce retinal vascular cell apoptosis. 100 Likewise, reduced levels of Cx43 are associated with retinal vascular lesions in human DR. 61 …”
Section: Connexinsmentioning
confidence: 66%
See 1 more Smart Citation
“…100 glucoseeinduced changes in Cx43 expression in human DR, and the potential application of this knowledge in the treatment of DR, is only beginning to be understood. Our findings demonstrated that high glucoseeinduced Cx43 up-regulation may have protective effects on retinal Müller cells, 99 whereas a decreased level of Cx43 alone is sufficient to induce retinal vascular cell apoptosis. 100 Likewise, reduced levels of Cx43 are associated with retinal vascular lesions in human DR. 61 …”
Section: Connexinsmentioning
confidence: 66%
“…99,100 Down-regulation of Cx43 expression subsequently decreases cell-cell communication to promote vascular cell death and vascular permeability under high glucose conditions. 100 glucoseeinduced changes in Cx43 expression in human DR, and the potential application of this knowledge in the treatment of DR, is only beginning to be understood.…”
Section: Connexinsmentioning
confidence: 99%
“…Müller cell ablation leads to photoreceptor degeneration, vascular leak, and intraretinal neovascularization demonstrating that Müller cells are necessary for both neuronal and vascular function and viability[29,43]. Changes to their environment by hyperglycemia alters functional interaction with pericytes[44]. Deletion of the dystrophin-Dp71 protein within Müller cells caused extensive vascular leakage and edema in the mouse retina.…”
Section: Release Of Growth Factors and Pro-/anti-inflammatory Cytokinmentioning
confidence: 99%
“…In addition, Cx43 is down-regulated in Müller glia in high glucose conditions, which leads to decreased gap junctions with pericytes and increased apoptosis in Müller glia and retinal microvascular endothelial cells (Li and Roy 2009; Muto et al 2014). Furthermore, retinas from diabetic or Cx43 heterozygous knockout mice develop retinal vascular lesions associated with diabetic retinopathies (Bobbie et al 2010).…”
Section: Xx3 Erp29 Connexin43 Trafficking and Gap Junctionsmentioning
confidence: 99%